DAKWAH COMMUNICATION STRATEGY TO MARGINAL PEOPLE: (Case Study of Marginal School Communities in Scavenger Settlements, Kledokan, Yogyakarta) - Fikriyatul Islami Mujahidah (Indonesian Journal of Islamic Communication, 2022)
The society growth of the digital world into a double-edged blade in the dakwah. The da 'i one side becomes easier on broadcasting the dakwah and can cover more mad’u. Unfortunately, it makes the lowlifes in this case a little neglected. So there is a need for upscale communication strategies to the marginal, as do the Sekolah Marginal Community (KSM). The study uses a qualitative approach with a descriptive case study method. Data collection methods involve interviews, observation, documentation, and case studies. The KSM uses the children's educational channel as a communication strategy for entry and preaching. In addition to education, the KSM also uses emotional approaches, changes mindset, serving various aspects of life, and performs evaluations.